Online Learning Challenges of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
The new normal way of education has reshaped the way learners engage with learning. During the pandemic, the learners engaged in distance learning, particularly online learning. The researchers observe that there are difficulties in this modality that needs to be understood. This study described the extent to which the respondents experience these difficulties which will be a basis for a proposed advocacy guide to help students navigate online learning more effectively. The researchers employed quantitative descriptive-correlational research designs, gathering the data from 107 junior high school students enrolled at Union Christian College during the school year 2021- 2022. The researchers used an adopted survey questionnaire to gather the data. Frequency count and percentage was used to present the profile of the respondents, while weighted mean was used in describing the extent to which the respondents experience online learning challenges. Pearson product moment correlation was used to determine the relationship between the variables. The findings highlight prevalent difficulties such as procrastination, technological competency issues, feelings of isolation, technological inadequacy, and distractions within the learning environment, underscoring the multifaceted nature of obstacles encountered in online education. Their challenges related to self-regulation, technological sufficiency, technological complexity, and learning resource is significantly related to their monthly family income, and sex. This means that limited financial capacity can lead to better access to technology for online learning. Furthermore, female respondents are more likely to encounter these challenges than male. The researchers conclude that the learners experience a variety of challenges that can make online learning more challenging. These insights are valuable to teachers as they can use these factors to elevate their online learning methods. The researchers recommend the adoption of the proposed advocacy guide for online learning to help the students overcome the challenges, and for teachers to promote ways to make online learning more fruitful and inclusive.
Keywords: online learning challenges; new normal education; distance learning